THE RELATIONSHIP BETWEEN HOMESICKNESS AND ACADEMIC MOTIVATION AMONG OVERSEAS STUDENTS IN KENDARI CITY: HOMESICKNESS AND ACADEMIC MOTIVATION - Nyfhodora, Fristy; Manduapessy, Advenia Tifany; Sugiarti, Lucia Rini; Suhariadi, Fendy (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: The phenomenon of students studying away from home, or what is often referred to as overseas students, is becoming increasingly common today. Students who migrate often experience homesickness which then affects their academic motivation. This study aims to prove whether there is a negative relationship between homesickness and academic motivation among overseas students in Kendari City. Methods: This research uses a qualitative method with accidental sampling as the sampling technique. 150 students were selected as subjects. Data collection used Homesickness Questionnaire by Archer and Academic Motivation Scale by Vallerand. Results: The result of the correlation coefficient analysis is -0.090 with a significance value of 0.275 (p> 0.05). The results showed that there is a negative relationship between homesickness and academic motivation in overseas students in Kendari City. Conclusion: The homesickness did not affect to academic motivation in overseas students in Kendari City.